Origin and transit migration of Afghans and Syrians to Germany: The influential actors and factors behind the destination choice - Masooma Torfa; Salwa Almohamed; Regina Birner (International Migration, 2021)
We use Process Net-Maps to visualize the irregular migration patterns of refugees and identify influential actors/factors shaping their decisions. A qualitative case study was used that included 87 Afghan and Syrian refugees (52 individual in-depth interviews and 35 participants in five focus group discussions) residing in Stuttgart, Germany. Results show a typical pattern for respondents to first migrate to a neighboring country, and then a mixture of decisive factors induce them to migrate onward. The perspective of refugees in the destination country covers the migration processes between transit and destination countries which is vital information for the stakeholders in international migration management, and policy developments on asylum migration, integration and repatriation.
Keywords: 300